Investigation of 3% Binahong (Anredera cordifolia) Leaf Extract Nanogel on the Alveolar Bone Healing: BMP-2 Modulation in Rat Models - Bernard, Bernard; Syafruddin Ilyas; Olivia Avriyanti Hanafiah (HM Publisher, 2024)
Background: Alveolar bone healing relies on osteoblasts activity and differentiation, with bone morphogenetic protein-2 (BMP-2) playing a crucial regulatory role. Binahong leaf extract (BLE) has demonstrated efficacy in bone healing due to its rich phytochemical composition. Nanogel offers enhanced bioavailability and targeted release to effectively deliver therapeutic agents. This study aims to assess the impact of 3% BLE nanogel on BMP-2 expression in tooth extraction socket healing. Methods: Thirty male Wistar rat underwent anaesthesia for the extraction of their lower incisors to induce alveolar bone healing. Subjects were randomly assigned into treatment (BLE nanogel) and control (base nanogel) group. Five rats from each group were respectively sacrificed at 7, 14, and 28 days after procedures. BMP-2 expression was assessed by performing immunohistochemistry analysis using BMP antibody reagent. Data were analysed using chi-square. Results: The analysis of BMP-2 expression showed no significant difference between treatment and control groups on days 7, 14, and 28 (p>0,05). However, a subtle increase was observed in the treatment group throughout observation period. Conclusion: Application of 3% BLE nanogel may enhance the expression of BMP-2, even though it was not significantly increase. The findings underscore the complex interplay between Binahong leaf extract, nanogel and BMP-2 expression.